2007
DOI: 10.1016/j.dnarep.2007.04.005
|View full text |Cite
|
Sign up to set email alerts
|

X-rays induce distinct patterns of somatic mutation in fetal versus adult hematopoietic cells

Abstract: There are a variety of mechanisms and pathways whereby cells safeguard their genomes in the face of environmental insults that damage DNA. Whether each of these pathways is equally robust at specific developmental stages in mammals and whether they are also modulated in a tissue-specific manner, however, are unclear. Here we report that ionizing radiation (IR) produces different types of somatic mutations in fetal cells compared with adult cells of the same lineage. While 1 Gy of Xray significantly induced int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Nuclear extracts were prepared as previously described [24], and an in-vitro BER assay that measures the short patch BER efficiency of cell extracts was performed [25]. Briefly, a 30-mer oligonucleotide 5′-GAGCCGGCACTGG U GCCCAGCTGATATCGC-3′ containing a uracil at position 14 (underlined) was annealed to the oligonucleotide 5′-GCGATATCAGCTGGGCGCCAGTGCCGGCTC-3′.…”
Section: Methodsmentioning
confidence: 99%
“…Nuclear extracts were prepared as previously described [24], and an in-vitro BER assay that measures the short patch BER efficiency of cell extracts was performed [25]. Briefly, a 30-mer oligonucleotide 5′-GAGCCGGCACTGG U GCCCAGCTGATATCGC-3′ containing a uracil at position 14 (underlined) was annealed to the oligonucleotide 5′-GCGATATCAGCTGGGCGCCAGTGCCGGCTC-3′.…”
Section: Methodsmentioning
confidence: 99%
“…If spontaneous mutations leading to LOH at Aprt primarily occur at earlier stages of hematopoietic development, but not in the mature T cells, an assessment of apoptosis in the mature T cells may not necessarily reflect the true nature of the target cells in which mutations arise. Indeed, while x-rays applied to adults preferentially induce deletions and point mutations, they primarily induce mitotic recombination when applied to fetus [24], suggesting that mitotic recombination, which accounts for the majority of the LOH events at Aprt , may primarily occur before birth.…”
Section: Resultsmentioning
confidence: 99%
“…In mice that were exposed to x-rays in their adulthood, there was a clear dose-dependent increase in the Hprt mutant frequency, but the increase in the Aprt mutant frequency was very modest. On the other hand, when x-rays was delivered to fetus in uteri, it had no effect on the Hprt mutant frequency, while Aprt mutant frequency was increased several fold, primarily due to an elevated mitotic recombination [24]. Interestingly, for reason(s) unknown, the mutational response to x-rays at Hprt is not affected by the status of apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…This has been supported by previous studies. Differentiated liver cells with high pol β expression exhibited stronger proliferative capacity with accumulation of base loss, misinsertion and/or base substitution than embryonic liver cells with wild-type level of pol β expression (Liang, et al, 2007). It’s also reported that increased pol β activity resulting from enhanced pol β mRNA and protein levels in various types of cancer tissues was remarkably higher than normal tissues (Albertella, et al, 2005).…”
Section: Discussionmentioning
confidence: 99%